2017
DOI: 10.1038/s41598-017-07141-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the broad substrate specificity of the human tyrosylprotein sulfotransferase-1

Abstract: Tyrosylprotein sulfotransferases (TPSTs) are enzymes that catalyze post-translational tyrosine sulfation of proteins. In humans, there are only two TPST isoforms, designated TPST1 and TPST2. In a previous study, we reported the crystal structure of TPST2, which revealed the catalytic mechanism of the tyrosine sulfation reaction. However, detailed molecular mechanisms underlying how TPSTs catalyse a variety of substrate proteins with different efficiencies and how TPSTs catalyze the sulfation of multiple tyrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 33 publications
(38 reference statements)
2
38
0
Order By: Relevance
“…Analysis of a variety of synthetic peptides and intact proteins confirms that TPST1 and TPST2 can also control site-specific sulphation on multiple tyrosine residues, which are often clustered, consistent with a processive mechanism of modification [7, 27], or directionally distributed towards the substrate N-terminus [20, 28]. Crystal structures of TPST1 complexed with substrate peptides that are sulphated with different efficiencies have also been reported, and comparative analysis suggests differential substrate preferences for acidic residues adjacent to the site of modification [24, 29]. Structural comparison suggests a shared catalytic mechanism and substrate-binding energetics, driven by charge-based dynamic interactions.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Analysis of a variety of synthetic peptides and intact proteins confirms that TPST1 and TPST2 can also control site-specific sulphation on multiple tyrosine residues, which are often clustered, consistent with a processive mechanism of modification [7, 27], or directionally distributed towards the substrate N-terminus [20, 28]. Crystal structures of TPST1 complexed with substrate peptides that are sulphated with different efficiencies have also been reported, and comparative analysis suggests differential substrate preferences for acidic residues adjacent to the site of modification [24, 29]. Structural comparison suggests a shared catalytic mechanism and substrate-binding energetics, driven by charge-based dynamic interactions.…”
Section: Introductionmentioning
confidence: 83%
“…The chemical similarity between the phosphate donor ATP and PAPS, the universal sulphate donor, led us to investigate whether peptide tyrosyl sulphation could be detected using a high-throughput enzymatic procedure previously validated for phosphorylation catalysed by ATP-dependent kinases. To isolate pure, enzymatically active recombinant TPST1 and TPST2, both were expressed at high levels in bacteria, and refolded after purification from inclusion bodies using published ‘slow’ procedures suitable for structural and enzymatic analysis of TPST1 [24] and TPST2 [29]. The affinity of our TPST1 and TPST2 preparations for the PAPS co-factor was found to be almost identical to that previously reported, and we confirmed that TPST1 and TPST2 were folded and could bind to a variety of physiological and non-physiological ligands.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations